2021
DOI: 10.3390/ijerph18042059
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine the Dietary Diversity Score in Rural Households: The Case of the Paute River Basin of Azuay Province, Ecuador

Abstract: Inadequate food and nutrition affect human well-being, particularly for many poor subpopulations living in rural areas. The purpose of this research was to analyze the factors that determine the Household Dietary Diversity Score (HDDS) in the rural area of the Paute River Basin, Azuay Province, Ecuador. The sample size of 383 surveys was determined by a stratified random sampling method with proportional affixation. Dietary diversity was measured through the HDDS, with 12 food groups (cereals; roots and tubers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 59 publications
7
30
0
5
Order By: Relevance
“…The low consumption of animal products could be due to higher prices attached to such commodities compared to vegetables and other food items. This result was similar to [38,43] who also found that consumption of food rich in micronutrients such as milk/dairy products and fish and seafoods is low in the study area. Meanwhile, the frequency of vegetables' consumption in the study area is high.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The low consumption of animal products could be due to higher prices attached to such commodities compared to vegetables and other food items. This result was similar to [38,43] who also found that consumption of food rich in micronutrients such as milk/dairy products and fish and seafoods is low in the study area. Meanwhile, the frequency of vegetables' consumption in the study area is high.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the study show that the diet of the sample UIVs producers in the study area is based on starch. This result is consonant with [38,43], who also reported a cereal-based diet for the sample respondent. It is noteworthy that the diets of the UIVs producers lacked protein-source products (such as eggs (1.5), milk and dairy products (2.1), fish and other seafoods (5.5), and meats (5.7)), which was an indicator that the households' diets lacked the important nutrients requirement by the body.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations